Research 101: A process for developing local guidelines for ethical research in heavily researched communities - Scott D. Neufeld; Jule Chapman; Nicolas Crier; Samona Marsh; Jim McLeod; Lindsay A. Deane (BMC, 2019)
Abstract Background Marginalized communities often attract more than their share of research. Too often, this research benefits researchers disproportionately and leaves such communities feeling exploited, misrepresented, and exhausted. The Downtown Eastside (DTES) neighborhood of Vancouver, Canada, has been the site of multiple public health epidemics related to injection drug use as well as the site of much community-led resistance and struggle that has led to the development of cutting-edge harm reduction interventions (e.g., North America's first supervised injection facility, Insite) and a strong sense of community organization. This background has made the DTES one of the most heavily researched communities in the world. Amidst ongoing experiences of unethical or disrespectful research engagement in the neighborhood, a collaboration between local academic researchers and community representatives developed to explore how we could work together to encourage more respectful, community-responsive research and discourage exploitative or disrespectful research. Methods We developed a series of six weekly workshops called "Research 101." These workshops brought together approximately 13 representatives from peer-based organizations in the DTES with a variety of experiences with research. Research 101 created space for community members themselves to discuss the pitfalls and potential of research in their neighborhood and to express community expectations for more ethical and respectful research. Results We summarized workshop discussions in a co-authored "Manifesto for Ethical Research in the Downtown Eastside." This document serves as a resource to empower community organizations to develop more equitable partnerships with researchers and help researchers ground their work in the principles of locally developed "community ethics." Manifesto guidelines include increased researcher transparency, community-based ethical review of projects, empowering peer researchers in meaningful roles within a research project, and taking seriously the need for reciprocity in the research exchange. Conclusions Research 101 was a process for eliciting and presenting a local vision of "community ethics" in a heavily researched neighborhood to guide researchers and empower community organizations. Our ongoing work involves building consensus for these guidelines within the community and communicating these expectations to researchers and ethics offices at local universities. We also describe how our Research 101 process could be replicated in other heavily researched communities.